Dietary protein requirements of physically active individuals - Paul, G. L. (Sports Medicine, 1989)
The dietary protein requirement of physically active individuals has received considerable scrutiny in recent years. Because the current United States Recommended Daily Allowance (USRDA) for protein (0.8 g/kg/day) already contains a safety margin (0.35 g/kg/day) to assure adequate protein intake, no increment in the USRDA was thought necessary to meet the demands of physical activity. Recently, collective evidence from research techniques utilising nitrogen balance, labelled amino acid isotopes, urea production and 3-methylhistidine excretion indicates that exercise (endurance and weightlifting) can significantly alter protein metabolism and that the dietary protein needs of physically active individuals may exceed the current USRDA. During endurance exercise, protein synthesis is depressed and protein degradation increases. Thus, amino acids become available for oxidation in energy-yielding processes. Amino acid catabolism has been estimated to contribute between 5 and 15% of the energy required during endurance exercise. Definitive conclusions regarding the changes that occur in protein synthesis and protein degradation during weightlifting exercise must await further research. The net contribution of amino acids to the energy required during weightlifting exercise is unknown but, due to the anaerobic nature of the event, it is most likely less than during endurance exercise. However, following both endurance and weightlifting exercise, protein synthesis increases. Based on current research, it is not yet possible to make recommendations for the daily protein needs of exercising individuals. It does appear that physically active individuals require more dietary protein per kilogram of bodyweight than sedentary individuals. However, when protein intake is expressed as a percentage of daily energy intake, physically active and sedentary individuals have similar requirements (approximately 12 to 15% of total energy as protein). Therefore, to cover the protein requirements of both physically active individuals and sedentary individuals it is suggested that future protein allowances be based on a percentage of the daily energy requirements. Protein consumption in excess of the current USRDA may minimise changes in body nitrogen stores, particularly during the first few weeks of training. However, further research is needed before a definitive conclusion can be made regarding protein ingestion and athletic performance.